2020
DOI: 10.3390/molecules25122746
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Juniperus indica Bertol Synergizes with Cisplatin to Inhibit Oral Cancer Cell Growth via Repression of Cell Cycle Progression and Activation of the Caspase Cascade

Abstract: Oral cancer—a type of head and neck cancer—is estimated to be the fifth most common cancer in Taiwan. However, efficacious therapies for oral cancer are still lacking due to drug resistance and recurrence. Consequently, the identification of new anticancer agents for clinical treatment is needed. Juniperus indica Bertol is a plant of the Juniperus genus often used as a treatment in traditional medicine due to its anti-inflammatory, antibacterial and diuretic functions. The biofunctions of Juniperus indica Bert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Cisplatin is commonly used for the treatment of diverse cancers, such as lung cancer, cervical cancer, osteosarcoma, and neuroblastoma . Although cisplatin shows good therapeutic effect, severe adverse side effects still exist, such as nausea, vomiting, peripheral neuropathy, and nephrotoxicity . Moreover, drug resistance may develop during the treatment, necessitating higher doses to achieve good effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cisplatin is commonly used for the treatment of diverse cancers, such as lung cancer, cervical cancer, osteosarcoma, and neuroblastoma . Although cisplatin shows good therapeutic effect, severe adverse side effects still exist, such as nausea, vomiting, peripheral neuropathy, and nephrotoxicity . Moreover, drug resistance may develop during the treatment, necessitating higher doses to achieve good effects.…”
Section: Discussionmentioning
confidence: 99%
“…These side effects require lowering the dose of cisplatin . Thus, the combination use of cisplatin with complementary and alternative herbal medicines is increasing worldwide . For example, in combination with l -canavanine, the IC 50 of cisplatin against Caco-2 cells could be decreased .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al [5] draw attention to the prospects of combination therapy as a new trend in the treatment of oral cancer (a type of head and neck cancer). The authors demonstrated for the first time that crude extract of liquid oil from Juniperus indica (a plant species famous in the traditional medicine of Taiwan) exhibited anticancer capacity.…”
mentioning
confidence: 99%